2020
DOI: 10.1007/s11926-020-00932-5
|View full text |Cite
|
Sign up to set email alerts
|

Work Disability in Axial Spondyloarthritis

Abstract: Purpose of Review Axial spondyloarthritis (axSpA) is a chronic inflammatory disease that typically affects people of working age. Work-related outcomes are therefore important to study, both from an individual but also a societal perspective. Through this review of the literature, we explore the impact of axSpA on key work outcomes including work and productivity loss and predictors for these. Recent Findings Recent evidence confirms that axSpA is associated with substantial consequences on the ability to work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 43 publications
1
18
1
Order By: Relevance
“…38 In line with most of the more recent clinical trial data, the meta-analysis by Shim et al did not show significant improvements in absenteeism with the use of biologics, despite improvements in presenteeism, work impairment and activity impairment. 44 This is in contrast to our findings in Chapter 4, which were mainly based on observational studies and showed positive effects with the use of biological therapies, although not always statistically tested. Future real-life observational data from controlled cohort studies are necessary to clarify these conflicting results.…”
Section: Prevention Of Adverse Work Outcomescontrasting
confidence: 99%
See 1 more Smart Citation
“…38 In line with most of the more recent clinical trial data, the meta-analysis by Shim et al did not show significant improvements in absenteeism with the use of biologics, despite improvements in presenteeism, work impairment and activity impairment. 44 This is in contrast to our findings in Chapter 4, which were mainly based on observational studies and showed positive effects with the use of biological therapies, although not always statistically tested. Future real-life observational data from controlled cohort studies are necessary to clarify these conflicting results.…”
Section: Prevention Of Adverse Work Outcomescontrasting
confidence: 99%
“…Since the publication of our review at least six new longitudinal studies have been published on this topic; 5 RCTs some including long-term extensions, and 1 observational cohort, all showing a positive influence of biological therapies on work-related outcomes in axial SpA. [38][39][40][41][42][43] Some of these studies have recently been reviewed narratively by Nikiphorou et al 44 The study by Shim et al is of particular interest because it provides reallife observational data investigating the impact of biological therapies on presenteeism and sick leave in the longer-term. 38 They used the large British Society for Rheumatology Biologics Register (BSRBR, n = 577) to show that axial SpA patients starting biological therapy at the time of recruitment experienced significantly greater improvements in work outcomes as compared to matched controls not treated with a biological.…”
Section: Prevention Of Adverse Work Outcomesmentioning
confidence: 99%
“…Axial spondyloarthritis (axSpA) is a disease of young individuals, typically of working age. 1 Studies to date suggest substantial consequences of disease on work-related outcomes. Many studies, however, have tended to focus on established disease and on a more permanent adverse outcome, work disability.…”
Section: Introductionmentioning
confidence: 99%
“…In a study on rheumatoid arthritis (RA) patients, higher disease activity was found to be related to decreased work productivity and quality of life (3). A recent review on work productivity in patients with spondyloarthritis (SpA) have reported significant relationship between productivity impairment and increased disease activity and functional status (8). Another study on 107 patients with psoriatic arthritis (PsA) reported a 6.7% decrease in work productivity and significant association between work loss and fatigue(4).…”
Section: Introductionmentioning
confidence: 99%